2015
DOI: 10.7554/elife.06807
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous interactions and protein disaggregases determine the material state of stress-inducible RNP granules

Abstract: RNA-protein (RNP) granules have been proposed to assemble by forming solid RNA/protein aggregates or through phase separation into a liquid RNA/protein phase. Which model describes RNP granules in living cells is still unclear. In this study, we analyze P bodies in budding yeast and find that they have liquid-like properties. Surprisingly, yeast stress granules adopt a different material state, which is reminiscent of solid protein aggregates and controlled by protein disaggregases. By using an assay to ectopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
612
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 516 publications
(657 citation statements)
references
References 83 publications
(161 reference statements)
26
612
4
Order By: Relevance
“…Prominent foci of Hsp104-positive aggregates were visible after 1 h. These Hsp104-positive protein aggregates were resistant to hexanediol (Panel C). This is in agreement with the finding that yeast stress granules, which colocalize with Hsp104 and depend on Hsp104 for dissolution [2], are insensitive to hexanediol (Panel C). We next tested whether actin filaments and microtubules are affected by hexanediol treatment (Panel D).…”
Section: Liquid-like But Not Solid-like Assemblies In Living Yeast Cesupporting
confidence: 82%
See 2 more Smart Citations
“…Prominent foci of Hsp104-positive aggregates were visible after 1 h. These Hsp104-positive protein aggregates were resistant to hexanediol (Panel C). This is in agreement with the finding that yeast stress granules, which colocalize with Hsp104 and depend on Hsp104 for dissolution [2], are insensitive to hexanediol (Panel C). We next tested whether actin filaments and microtubules are affected by hexanediol treatment (Panel D).…”
Section: Liquid-like But Not Solid-like Assemblies In Living Yeast Cesupporting
confidence: 82%
“…Hexanediol was shown to perturb FG repeat interactions between nucleoporins in nuclear pores [6] [7] and interactions between RNAbinding proteins in RNA-protein granules (RNP) [2] [8]. These studies suggested that 1,6-hexanediol interferes with weak hydrophobic protein-protein or protein-RNA interactions that are required for these dynamic, liquid-like assemblies to form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only at subsequent stages these droplets maturate into more stable structures that are more likely to incorporate functional amyloid. [122][123][124] In the framework of this model formation of amyloid might also manifest an alternative, strictly pathogenic pathway. 122,123 Consequently, the lack of negative selection toward the formation of amyloid by wild type or single-mutation proteins is explained either by the functionality of the amyloid state in the granules or exclusively by the need to maintain CBRs / LCRs prone for multivalent interactions.…”
Section: Prions Amyloids and Mrna Turnovermentioning
confidence: 99%
“…120,121 Even though the presence of multiple amyloidogenic proteins with CBRs / LCRs in P-bodies and stress granules led to the hypothesis that functional amyloids are implicated in the biogenesis of these RNPs, 45,111,118,119 so far there is no proof that these proteins are present in RNPs in the amyloid state. 122 Indeed, it appears that initial formation of these RNPs is enthalpy driven, depends on multivalent interactions involving both CBRs/LCRs and RNAbinding domains of proteins and RNAs, and leads to the formation of large RNP complexes in extremely dynamic phase-separated liquidlike droplets. Only at subsequent stages these droplets maturate into more stable structures that are more likely to incorporate functional amyloid.…”
Section: Prions Amyloids and Mrna Turnovermentioning
confidence: 99%